The Effect of Project-Based Learning with the Science, Technology, and Society Approach on Digestive System Material Against the Concept Mastery - I Putu Artayasa; Jihan Juliastari; I Wayan Merta (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to examine the effect of a project-based learning model with a science, technology, and society approach to students' mastery of class VIII concepts. This type of research is a quasi-experimental type using a non-equivalent control group design. The population of the study was students of SMP Negeri 7 Mataram for the 2021/2022 academic year with a sample consisting of 74 class VIII students. The data obtained were analyzed using the Covariate Analysis test (anacova) with reference to a significance level of 0.05. The results of the study show that the sig. (p) = 0.000 less than alpha 0.05, so it can be concluded that the project-based learning model with a science and technology community approach has a significant effect on junior high school students' conceptual understanding.